Current situation and tasks for public health and medical cooperation between South Korea and Central Asia: Focusing on Kazakhstan and Uzbekistan - Sunmi Jung (Journal of Eurasian Studies, 2022)
2022 marks the 30th anniversary of diplomatic ties between Korea and Central Asia. Since the establishment of diplomatic ties, Korea and Central Asia have expanded exchanges in various fields, including politics, economy, and diplomacy. Cooperation between Korea and Central Asia utilizing the abundant medical manpower of Central Asia and Korea’s excellent medical and pharmaceutical technology was also selected as a promising area of cooperation between the two sides. Korea and Central Asia have continued to cooperate in the field of health and medical care, but there were limits to deepening cooperation. Recently, the importance of health and medical cooperation around the world has been highlighted again due to COVID-19. This thesis examines the status and problems of health care in Central Asia, and analyzes the achievements and limitations of health care cooperation between Korea and Central Asia. The purpose of this is to suggest directions for strengthening health care cooperation between Korea and Central Asia. This will help the new government, which aims to become a global center of bio-digital health, explore strategies and policies for preemptive health care cooperation in Central Asian countries.